Unusual presentation of Chronic Subdural hematoma as Isolated Oculomotor palsy - Shrestha, Janam; Rajbhandari, Pravesh; Gurung, Pritam; Sharma, Upama; Malla, Samriddha; Pant, Basant (Nepal Journal of Neuroscience, 2023)
Isolated oculomotor palsy (ONP) is an unusual presentation in chronic subdural hematomas (CSDH) and is very rare as an initial manifestation. Most commonly, ONP is caused by ischemic microangiopathy, posterior communicating artery aneurysm, uncal herniation, neoplasia, traumatic and/or any inflammatory conditions. ONP in chronic subdural hematoma is a sign of cerebral herniation that is typically associated with a deterioration of consciousness. We describe a case of chronic subdural hematoma that presented with an isolated ONP.